Auditory free classification of nonnative speech - Atagi, Eriko (2013)
Through experience with speech variability, listeners build categories of indexical speech characteristics including categories for talker, gender, and dialect. The auditory free classification task—a task in which listeners freely group talkers based on audio samples—has been a useful tool for examining listeners’ representations of some of these characteristics including regional dialects and different languages. The free classification task was employed in the current study to examine the perceptual representation of nonnative speech. The category structure and salient perceptual dimensions of nonnative speech were investigated from two perspectives: general similarity and perceived native language background. Talker intelligibility and whether native talkers were included were manipulated to test stimulus set effects. Results showed that degree of accent was a highly salient feature of nonnative speech for classification based on general similarity and on perceived native language background. This salience, however, was attenuated when listeners were listening to highly intelligible stimuli and attending to the talkers’ native language backgrounds. These results suggest that the context in which nonnative speech stimuli are presented—such as the listeners’ attention to the talkers’ native language and the variability of stimulus intelligibility—can influence listeners’ perceptual organization of nonnative speech.